IS SOCIAL WORK A PRIORI HUMANE IN ITS NATURE? - Milosavljević, Milosav (Politeia, 2019)
Social work is an activity and profession that has passed through various phases in its development, taking on different forms (traditional-positivist, functionalist, bureaucratic, radical). The character of social work can be judged on the basis of what its goals are, on which values and principles it is founded; what its relations towards citizens, service users, colleagues, and members of related professions and local communities are, as well as on the basis of means, methods, and skills it uses in its practice. At the beginning of the 21st century, social work follows the pluralism of ideas, concepts, models, experiences, and practices, as well as it faces new and complex challenges and problems arising from the processes of globalisation and diversification, as generally complex processes in their nature, which, in turn, create even more complex social problems, but, at the same time, narrow down institutional, economic, political, and cultural opportunities for social work. The author claims that there are solid ideological and value bases, ideas, theories, and good practice experiences for the development of humanistic or integrative social work, but their realisation depends on the economic, political, cultural, and social context of concrete societies, and on the will and power of social workers to establish their work on humanistic grounds. It is the general conclusion of this paper that social work is not humane a priori, which means that we still need to create such social conditions in order to direct goals, contents, methods, procedures, and attitudes of social work towards the affirmation, well-being and welfare of human beings in practice.